The role and place of Taiwan in the transformation of the Asia-pacific security system - Burtsev, D.; Бурцев, Д. (Поліграф-Сервіс, 2024)
Starting from Nancy Pelosi's visit to Taiwan in 2022, the topic of Taiwan as a new possible military hotspot became more and more discussed in various international contexts that are related to international and regional security in the Asia-Pacific. The competition between the United States and China has become the competition of the global scope even before 2022 because of numerous factors. The main concern comes from the question of the probability of a conflict in the Taiwan Strait between Taiwan and the People's Republic of China and dragging not only other regional actors into this possible conflict but also the possible role of the United States in case such conflict occurs. Починаючи з візиту Ненсі Пелосі до Тайваню у 2022 році, тема Тайваню як нової можливої військової точки дедалі більше обговорювалося в різних міжнародних контекстах, пов’язаних з міжнародною та регіональною безпекою в Азіатсько-Тихоокеанському регіоні. Конкуренція між США і Китаєм набула глобального масштабу ще до 2022 року через численні фактори. Основне занепокоєння виникає через питання ймовірності конфлікту у Тайванській протоці між Тайванем і Китайською Народною Республікою та втягування не лише інших регіональних учасників у цей можливий конфлікт, а й самих Сполучених Штатів у разі виникнення такого конфлікту.
Роль і місце Тайваню в трансформації системи безпеки Азійсько-Тихоокеанського регіону
Keywords: security system; Taiwan; international security; regional security; система безпеки; Тайвань; міжнародна безпека; регіональна безпека